Проблеми та досягнення у вивченні метаболічної хвороби кісток у дітей раннього віку (огляд літератури) - Боярська, Людмила Миколаївна; Овчаренко, Леонід Сергійович; Редько, Ірина Іванівна; Герасімчук, Тетяна Сергіївна; Левчук-Воронцова, Тетяна Олегівна; Boiarska, L. M.; Ovcharenko, L. S.; Redko, I. I.; Herasimchuk, T. S.; Levchuk-Vorontsova, T. O. (Запорізький державний медико-фармацквтичний університет, 2024)
Мета роботи – систематизувати та проаналізувати дані наукових досліджень, описати патофізіологічні механізми, що спричиняють розвиток метаболічних захворювань кісток у передчасно народжених дітей, а також здійснити пошук інноваційних підходів до діагностики та профілактики захворювання. Метаболічна хвороба кісток (неонатальна остеопенія) є складним медичним викликом під час надання допомоги недоношеним дітям, які народжені з дуже низькою масою тіла, та хворим немовлятам. Зусилля медичної спільноти спрямовані на максимальне збільшення щільності кісткової тканини в різні періоди росту, починаючи з внутрішньоутробного та неонатального періодів розвитку, для сприяння формуванню та збереженню кісткової тканини надалі. Aim. The aim of this work is to systematize and analyze scientific research data, to reveal pathophysiological mechanisms contributing to the development of metabolic bone diseases in premature infants, and to search innovative approaches to diagnosis and prevention of these disorders. Materials and methods. The study involved reviewing and analyzing domestic and foreign literature sources using the PubMed and Scopus databases for the period 2019–2024. The literature was searched and selected using the keywords: newborns, preterm infants, neonatal osteopenia, metabolic bone disease, and ultrasound densitometry. Full-text articles from studies with evidence levels I–II were included to this review in order to systematize and summarize the findings. Metabolic bone disease (neonatal osteopenia) presents a significant medical challenge in the care of preterm infants, especially those born with very low birth weight and sick neonates. The current requirements of the medical community are aimed to maximize bone density during growth periods, starting from the intrauterine and neonatal stages, to promote the formation and preservation of bone tissue in later life.
Problems and achievements in the study of metabolic bone disease in young children (literature review)
Боярська Л. М. - ORCID ID: 0000-0002-2297-7635; Овчаренко Л. С. - ORCID ID: 0000-0001-9711-1329; Редько І. І. - ORCID ID: 0000-0001-8165-7036; Герасiмчук Т. С. - ORCID ID: 0000-0001-5251-2444; Левчук-Воронцова Т. О. - ORCID ID: 0000-0003-4926-1271.
Keywords: діти; новонароджені; недоношені діти; неонатальна остеопенія; вітамін D3; кальцій; ультразвукова денситометрія; паратгормон; кальцитонін; children; newborns; preterm infants; neonatal osteopenia; vitamin D3; calcium; ultrasound densitometry; parathyroid hormone; calcitonin